PENGARUH SUKU BUNGA, NILAI TUKAR, DAN PERTUMBUHAN GDP TERHADAP INDEKS HARGA SAHAM DI BURSA EFEK INDONESIA DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Kasus Indeks Harga Saham Sektor Indurstri Barang Konsumsi Periode 2010 – 2020) - Islamiati, Dian; Herdiyana, Herdiyana; Hardiyanto, Arief Tri (Universitas Pakuan, 2023)
This research to determine the effect of interest rates, exchange rates, GDP growth on ROA and the effect of interest rates, exchange rates, GDP growth, ROA on stock prices of the consumer goods industry sector that listed on the Indonesia Stock Exchange (IDX)). The population in this study are the stock prices index in the consumer goods industry sector on the IDX during period 2010-2020. The sampling technique in this research is using a purposive sampling technique to produce 24 annual panel data samples during period 2010-2020. The analytical technique is using the panel data regression analysis. The results of this research are: 1) Interest rates do not have a significant effect on the profitability of companies in the consumer goods industry sector. 2) The exchange rate has a significant negative effect on the profitability of companies in the consumer goods industry sector. 3) GDP growth has no significant effect on the profitability of companies in the consumer goods industry sector. 4) Interest rates do not have a significant effect on the stock prices of companies in the consumer goods industry sector. 5) The exchange rate has a significant negative effect on the stock prices of companies in the consumer goods industry sector. 6) GDP growth has no significant effect on company stock prices in the consumer goods industry sector. 7) Profitability has a significant positive effect on company stock prices in the consumer goods industry sector. Based on the Adjusted R Square (R2) value in this research, the composite stock price index (IHSG) can be explained by the effect of variations in the independent variables of interest rates, exchange rates, GDP growth and profitability (ROA) of 84% meanwhile 16% is explained by other variables besides the variables in this research.